2022
DOI: 10.3390/foods11050734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of κ-Carrageenan and Guar Gum on the Rheological Properties and Microstructure of Phycocyanin Gel

Abstract: The effects of two polysaccharides on the performance and microstructure of phycocyanin gels were studied by choosing anionic polysaccharides (κ-carrageenan) and neutral polysaccharides (guar gum). The linear and nonlinear rheological properties and microstructure of the phycocyanin-polysaccharide composite gel were evaluated. The results show that both κ-carrageenan and guar gum can enhance the network structure of phycocyanin gel and weaken the frequency dependence. The sample with 0.4% κ-carrageenan has the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…This fact is a gel-type behavior, suggesting the creation of a 3D network for these systems. Previously, it has been said that k-carrageenan could enhance the network structure and weaken the frequency dependence in PC dispersions [ 18 ]. Hence, this behavior could be applied to emulsions systems based in PC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact is a gel-type behavior, suggesting the creation of a 3D network for these systems. Previously, it has been said that k-carrageenan could enhance the network structure and weaken the frequency dependence in PC dispersions [ 18 ]. Hence, this behavior could be applied to emulsions systems based in PC.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its applications in the food industry, kappa-carrageenan is also employed in cosmetic and pharmaceutical products, such as gels and creams, due to its capacity to retain water and improve product consistency [ 15 , 16 , 17 ]. Its use combined with PC has increased the viscoelastic properties and viscosity of the aqueous phase studies compared to PC systems [ 18 ]. Nevertheless, this combination has never been studied in emulsion systems.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment conducted in this research, the addition of kappa-carrageenan in the M3 encapsulating matrix significantly impacted the diffusion of CPC into the CaCl2 crosslinking solution, reducing it to below 20% and improving the CPC retention observed when agavins were added to the formulated mixtures (M2). Lei et al [25] studied mixtures of CPC and increasing concentrations of kappa-carrageenan, finding that the strongest interaction occurred through disulfide bonds, followed by hydrophobic and electrostatic forces, with a weaker interaction through hydrogen bonding. These interactions were important for the formation of CPC and CGN-based gels, as they resulted in a denser, less porous network with reduced hydrophilicity, thereby improving the retention of the hydrophilic CPC protein.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency sweep results indicate that G increased with the concentration of guar gum, possibly owing to the network structure of galactomannan and protein and hydrogen bonds. Lei et al [45] studied the effect of guar gum on the linear rheological properties of phycocyanin and found that samples containing guar gum had higher G and G values. Still, as the concentration increased, G and G decreased owing to the increased entanglement of galactomannan chains, which prevented interaction with proteins.…”
Section: Frequency Sweepmentioning
confidence: 99%